2012
DOI: 10.1002/ppul.22555
|View full text |Cite
|
Sign up to set email alerts
|

Clinical safety, pharmacokinetics, and efficacy of ambrisentan therapy in children with pulmonary arterial hypertension

Abstract: Summary Recent trials in adult PAH revealed the efficacy of ambrisentan. However, in children with PAH, the clinical safety and pharmacokinetics of ambrisentan has not been well studied. Our aim was to investigate the clinical safety, pharmacokinetics, tolerability, and efficacy of endothelin receptor antagonist therapy with ambrisentan in children with pulmonary arterial hypertension (PAH). This retrospective cohort study provides clinical data from pediatric patients with PAH receiving ambrisentan as add-on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 24 publications
2
53
0
1
Order By: Relevance
“…The most common side effects are nasal congestion and headaches. Ambrisentan has shown improvement of WHO-FC and hemodynamics in children with PAH, and some children can be safely switched from bosentan to ambrisentan [138].…”
Section: Endothelin Receptor Antagonists (Era)mentioning
confidence: 99%
“…The most common side effects are nasal congestion and headaches. Ambrisentan has shown improvement of WHO-FC and hemodynamics in children with PAH, and some children can be safely switched from bosentan to ambrisentan [138].…”
Section: Endothelin Receptor Antagonists (Era)mentioning
confidence: 99%
“…6,7) Pulmonary vasodilator therapy improves outcomes in patients with idiopathic PAH, and has also been reported to be effective in patients with other types of PAH. [8][9][10][11][12][13] This therapy may reduce pulmonary vascular resistance (Rp) in patients who were previously thought to have irreversible pulmonary vascular disease.…”
Section: R Ecent Advances In Pediatric Cardiac Surgery Techniquesmentioning
confidence: 99%
“…6,42) These vasodilators have been shown to improve functional status and survival in patients with idiopathic PAH. [6][7][8][9][10][11][12][13] Pulmonary vasodilator therapy is now being used to treat PAH in patients with CHD, including those with Eisenmenger syndrome. Many reports have indicated that the endothelin receptor antagonist bosentan is effective for improving clinical outcomes and exercise capacity in patients with Eisenmenger syndrome.…”
Section: How Does Pulmonary Vasodilator Therapy Affect Outcomes In Pamentioning
confidence: 99%
“…Ambrisentan, a selective ET A receptor blocker (which can be administered once a day and has been reported with no hepatotoxicity) was found to be efficacious in children with an acceptable safety profile. 24 Macitentan is a tissue-specific ERA that is now FDA approved for use in adult PAH, and studies in pediatric patients are ongoing.…”
Section: Inhaled Prostacyclin Analoguesmentioning
confidence: 99%